STRATEGI PENGEMBANGAN KOLEKSI DIGITAL E-LIBRARY UNIVERSITAS MUHAMMADIYAH PONOROGO - Naza Nur 'ulummi; Purwani Istiana; Ayu Wulansari (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2025)
This study aims to analyze the strategy of developing collections in the E-Library of the University of Muhammadiyah Ponorogo in facing the digital era. The research method used is qualitative with data collection techniques through interviews with E-Library librarians of the University of Muhammadiyah Ponorogo. The results of the study show that University of Muhammadiyah Ponorogo E-Library implements various strategies in the development of digital collections, including: (1) analysis of user needs through surveys, (2) digital resources through consortiums, grants, and independent purchases, (3) collaboration with other parties such as universities and digital platform providers, (4) utilizing various platforms and software, (5) promotion of digital collections through various channels, and (6) continuous evaluation of the collection. This study concludes that the E-Library of the University of Muhammadiyah Ponorogo has a strong commitment to developing digital collections to meet the information needs of the academic community. Despite facing challenges such as budget limitations, the E-Library of the University of Muhammadiyah Ponorogo is able to take strategic steps to ensure the availability of relevant and quality information resources.